THE DIFFERENCE IN SALES LEVELS DURING THE COVID-19 PANDEMIC AND AFTER THE COVID-19 PANDEMIC AT KEDAI LEMBAYUNG SURABAYA. - Wahyu Ratnasari; Mochammad Daffa Rizal Mahendra (Cerdika: Jurnal Ilmiah Indonesia, 2024)
This study evaluates the impact of the COVID-19 pandemic on Micro, Small, and Medium Enterprises (MSMEs), focusing on the food sales sector, especially at Kedai Lembayung Surabaya. In response to the pandemic, the government implemented Large-Scale Social Restrictions (PSBB), which significantly impacted the informal sector and MSMEs. Kedai Lembayung Surabaya, established in December 2020, suffered setbacks in revenue, scarcity of raw materials, and capital due to the pandemic. The purpose of this study is to evaluate the level of sales at Kedai Lembayung Surabaya during the COVID-19 pandemic and after, with the main aim of understanding the possible impact on sales performance. The research method uses Regression Analysis to evaluate the influence of various variables on business performance. The results showed a significant difference in food menu sales during the pandemic and post-pandemic. There is customer adaptation with an increase in online purchases through applications. Restaurant peak hours remain on the same pattern, focused on lunch hours. This research provides deep insights into the impact of the pandemic on culinary MSMEs, identifies changes in sales patterns, and shows the need for business strategy adaptation during crises.